2015
DOI: 10.1007/s10561-015-9517-6
|View full text |Cite
|
Sign up to set email alerts
|

The effective mode of growth and differentiation factor-5 in promoting the chondrogenic differentiation of adipose-derived stromal cells

Abstract: Our study aimed to find out the most effective mode for chondrogenic differentiation based on time, dose and culture method. ADSCs were cultured and identified by CD44, CD49d, and CD106 immumohistochemical staining method, and their differentiation potential to chondrocyte were detected by Alizarin red staining. ADSCs induced by different concentrations of GDF-5 for chondrogenic differentiation were detected by blue and toluidine blue staining and collagen type II and X immumohistochemical staining. The expres… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 23 publications
0
8
0
Order By: Relevance
“…Both GDF5 and GDF6 have also been shown to induce the expression of general chondrogenic genes (Sex determining region Y‐Box9 (SOX9); type II collagen; ACAN) and, importantly, to also induce NP‐specific genes (KRT18, KRT19, CA12, Brachyury (T), CD24, HIF1α, Glut‐1 and SHH) in MSCs and adipose‐derived stem cells (ASCs) (Table ). When GDF5 is added as a media supplement to high‐density cultures of MSCs or ASCs, chondrogenic differentiation is increased; however, several reports also note a significant increase in markers of hypertrophy and ossification including alkaline phosphatase, collagen types I and X, and osteopontin . These characteristics indicate a progression in expression reflective of chondrogenic hypertrophy toward endochondral ossification, which is undesirable for NP populations.…”
Section: The Effect Of Gdfs On the Differentiation Of Mscs Toward An mentioning
confidence: 99%
“…Both GDF5 and GDF6 have also been shown to induce the expression of general chondrogenic genes (Sex determining region Y‐Box9 (SOX9); type II collagen; ACAN) and, importantly, to also induce NP‐specific genes (KRT18, KRT19, CA12, Brachyury (T), CD24, HIF1α, Glut‐1 and SHH) in MSCs and adipose‐derived stem cells (ASCs) (Table ). When GDF5 is added as a media supplement to high‐density cultures of MSCs or ASCs, chondrogenic differentiation is increased; however, several reports also note a significant increase in markers of hypertrophy and ossification including alkaline phosphatase, collagen types I and X, and osteopontin . These characteristics indicate a progression in expression reflective of chondrogenic hypertrophy toward endochondral ossification, which is undesirable for NP populations.…”
Section: The Effect Of Gdfs On the Differentiation Of Mscs Toward An mentioning
confidence: 99%
“…Previous studies have found that GDF-5 promoted the recruitment of mesenchymal stem cells (MSCs) and their differentiation into chondrocytes, thus accelerating chondrogenesis and joint formation. 15,16 In recent years, GDF-5 has shown great application potential in bone tissue repair. GDF-5 deciency resulted in delayed bone healing, 17 whereas its addition promoted MSCs osteogenic differentiation and VEGF expression.…”
Section: Introductionmentioning
confidence: 99%
“…The procedure of immunohistochemical staining was described as previously. 14 Briefly, paraffin-embedded liver sections (5 μm thickness) were deparaffinized and rehydrated, then disposed with 3% H 2 O 2 for 10 min followed by blocking with 5% donkey serum for 30 min at room temperature, finally, incubated with primary antibodies against F4/80 (macrophage marker; cat No. ab16911; 1:200, Abcam, Cambridge, MA, USA), CD45 (leukocyte marker; cat No.…”
Section: Methodsmentioning
confidence: 99%